2021
DOI: 10.1038/s41598-021-00721-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual feedback improves bimanual force control performances at planning and execution levels

Abstract: The purpose of this study was to determine the effect of different visual conditions and targeted force levels on bilateral motor synergies and bimanual force control performances. Fourteen healthy young participants performed bimanual isometric force control tasks by extending their wrists and fingers under two visual feedback conditions (i.e., vision and no-vision) and three targeted force levels (i.e., 5%, 25%, and 50% of maximum voluntary contraction: MVC). To estimate bilateral motor synergies across mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Moreover, our correlation findings indicated that a decrease in V ORT across multiple trials with higher visual gain conditions was significantly related to less force error within a trial. These findings expand prior results in that bilateral motor synergies across multiple trials from no vision to vision conditions were associated with improved bimanual force control within a trial 34 . Improved bilateral force control strategies with increased visual gain is typically observed when a surgeon is performing an operation using microscopic surgery techniques 47 , 48 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, our correlation findings indicated that a decrease in V ORT across multiple trials with higher visual gain conditions was significantly related to less force error within a trial. These findings expand prior results in that bilateral motor synergies across multiple trials from no vision to vision conditions were associated with improved bimanual force control within a trial 34 . Improved bilateral force control strategies with increased visual gain is typically observed when a surgeon is performing an operation using microscopic surgery techniques 47 , 48 .…”
Section: Discussionsupporting
confidence: 85%
“…To stabilize task performances (i.e., greater V Index ), the motor system may select one of three strategies: (a) increased flexibility (higher V UCM ) of elemental variables without changes in stability (V ORT ), (b) increased stability (lower V ORT ) of elemental variables without changes in flexibility (V UCM ), and (c) increased both flexibility (higher V UCM ) of elemental variables and stability (lower V UCM ). Our recent findings revealed that the presence of visual feedback using two visual gain conditions (i.e., 13 pixels/N at 5% of MVC and 8 pixels/N at 25% and 50% of MVC) improved bilateral motor synergies with decreased bad variance as compared with no vision condition 34 . These findings suggested that the availability of visual information during bimanual force control may facilitate the motor system to increase the stability patterns (i.e., a reduction of bad variance) across multiple trials stabilizing task performances.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Current research argues that force accuracy between intended and actual force can be increased by visual feedback 65 . We deliberately did not use visual feedback in the present experiment for two reasons.…”
Section: Limitations and Future Study Considerationsmentioning
confidence: 99%